PERSONALITY IN MICHAEL PUNKE’S NOVEL THE REVENANT: A NOVEL OF REVENGE - Syahruddin Said; Sri Chairani; M. Manugeren; Purwarno Purwarno (Universitas Islam Sumatera Utara, 2023)
This study is the result of a library research which is qualitative in nature on the bravery and strength of the protagonist named Hugh Glass depicted in Michael Punke’s The Revenant; overall exposing the social phenomena tied to personality. Concepts about the protagonist and personality covering bravery and strength are highlighted to support the analysis. The research findings show that the protagonist’s bravery and strength are found in the novel and have helped him much to survive in the wild woods when he is abandoned by his two friends named Fitzgerald and Bridger, who prove themselves to be unreliable. Fitzgerald and Bridger not only abandon him but also rob all his belongings that he needs to survive in the wild woods. In his serious wounds and state of dying added with no rifle, hatchet, knife and flint and steel, Glass eventually overcomes the obstacles in the wild woods, and survive to materialize his ambitions.